Implementation Of School-Based Management In The Formation Of Character Of State Elementary School Students 1 Watu Belah - Fikriyah, Fikriyah; Saifullah Hafizh, Azhar; Hadistia, Pipih; Ayuzana Az-Zahra, Rahma; Aufha, Eriska (Jurnal Edusci, 2024)
Character education is more important than moral education because character education not only recognizes what is right and what is wrong but also how students are subjected to goodness. Character education includes education of values, ethics, morals, and character and aims to teach students how to make good choices and maintain goodness in daily life. This study aims to determine how the implementation of character-based school management in SDN 1 Watubelah runs. This study uses a qualitative approach with data collection techniques: in-depth interviews, observations, and audiovisuals. The criteria used to select informants are homeroom teachers, BK teachers, and curriculum staff. The study results show that schools want to instill traits such as creativity, talent, and morals. They also do not forget basic traits such as honesty, discipline, etc